A Moexitecan Magnetic Liposomal Strategy for Ferroptosis-Enhanced Chemotherapy - Weiling Miao; Yang Liu; Jian Tang; Tiandong Chen; Fang Yang (MDPI AG, 2023)
Moexitecan (Mex) is a novel camptothecin derivative that retains the potent antitumor properties of camptothecin drugs and has improved hydrophilicity to enhance biocompatibility in vitro. However, single-drug therapy still has limitations. In this study, magnetic liposomes loaded with both moexitecan and superparamagnetic iron oxide nanoparticles (SPIO) have been fabricated by a film hydration and filtration method, which is abbreviated as Mex@MLipo. By using liposomes as drug carriers, Mex can be delivered specifically to the target site, resulting in improved therapeutic efficacy and reduced toxicity. Morphology characterization results show that Mex@MLipo has a mean diameter of 180-200 nm with a round morphology. The loading efficiencies of Mex and SPIO are 65.86% and 76.86%, respectively. Cell toxicity, in vitro cell uptake, and in vivo fluorescence imaging experiments showed that Mex@MLipo was the most effective in killing HT-29 cells compared with HepG-2 and PC-3 cells, due to its ability to combine chemotherapy and induce ferroptosis, resulting in a strong anti-tumor effect. Thus, this study developed an innovative nanoscale drug delivery system that paves the way for clinical applications of moexitecan.